2010
DOI: 10.1051/vetres/2010043
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic characteristics of persistent feline enteric coronavirus infection in cats

Abstract: Feline coronaviruses (FCoV) comprise two biotypes: feline enteric coronaviruses (FECV) and feline infectious peritonitis viruses (FIPV). FECV is associated with asymptomatic persistent enteric infections, while FIPV causes feline infectious peritonitis (FIP), a usually fatal systemic disease in domestic cats and some wild Felidae. FIPV arises from FECV by mutation. FCoV also occur in two serotypes, I and II, of which the serotype I viruses are by far the most prevalent in the field. Yet, most of our knowledge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
103
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(118 citation statements)
references
References 25 publications
(46 reference statements)
14
103
0
1
Order By: Relevance
“…Shortly thereafter additional studies using the same assay demonstrated replicating forms of RNA in the blood of healthy cats infected with FECV (Can-Sahna et al, 2007;Kipar et al, 2010), casting doubts on the specificity of such tests. The ability of FECV to replicate in blood monocyte/macrophages was also reported by other groups (Vogel et al, 2010). Chang et al (2012) subsequently identified two specific mutations within the fusion peptide of the spike protein of FIPVs that were not present in parent FECVs.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…Shortly thereafter additional studies using the same assay demonstrated replicating forms of RNA in the blood of healthy cats infected with FECV (Can-Sahna et al, 2007;Kipar et al, 2010), casting doubts on the specificity of such tests. The ability of FECV to replicate in blood monocyte/macrophages was also reported by other groups (Vogel et al, 2010). Chang et al (2012) subsequently identified two specific mutations within the fusion peptide of the spike protein of FIPVs that were not present in parent FECVs.…”
Section: Introductionsupporting
confidence: 62%
“…However, closer examination of these studies indicates that detection of feline coronavirus genomic RNA has not been as clear-cut as assumed, mainly because detection is often at or beyond the limits of reliability for the assay procedure. Three studies reported on the detection of feline coronavirus RNA in blood, but all were concerned with FECV rather than FIPV infection and detection was inconsistent (Meli et al, 2004;Kipar et al, 2010;Vogel et al, 2010). Kipar et al (2001Kipar et al ( , 2006 compared virus loads in various tissues, excluding blood, in naturally infected cats and indicated that virus loads were higher in FIPV than FECV infected cats.…”
Section: Discussionmentioning
confidence: 99%
“…FPV infects rapidly dividing cells, including lymphoid tissue and proliferating cells of the bone marrow resulting in cell lysis and functional immunosuppression which predisposes these animals to other infectious agents (Truyen et al, 2009). FCoV causes a mild diarrhoea and coinfects cats with T. foetus (Paris et al, 2014;Vogel et al, 2010). FCoV may have contributed to the increased T. foetus burden, however, its role was likely minor in the face of severe feline parvoviral enteritis.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in the ability of the PEDV to reach the vascular system may be associated with the viral strain (Park and Shin, 2014). Sporadic detection of viral RNA of another enteric coronavirus, feline enteric coronavirus (FECV), in blood seems to be associated with mononuclear cells that engulf the virus in the gut and subsequently gain access to the vascular system (Vogel et al, 2010). The susceptibility of mononuclear cells to FECV is however poor and viral spread is inefficient (Rottier et al, 2005).…”
Section: Discussionmentioning
confidence: 99%